CHRONIC PURULENT RHINOSINUSITIS: A REVIEW OF THE MEDICAL LITERATURE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Inflammatory pathology of the ENT organs accounts for 87% of all visits to the otorhinolaryngologist, in the last decade the incidence of paranasal sinusitis (PNS) has increased, and the proportion of hospitalized patients with this pathology has increased almost 3 times every year. The problem of timely diagnosis and treatment of PNS is currently quite relevant, despite the emergence of new modern methods of conservative and surgical treatment. According to various authors, PNS currently ranks first among inflammatory diseases of the upper respiratory tract. The paranasal sinuses (SNS) are a single morphological and functional system with similar etiological factors and mechanisms for the development of diseases, therefore, when studying the epidemiology of the PNS, it is necessary to assess the prevalence of diseases not only of each sinus separately, but also of their combined lesions.